Maternal and Child Health: The Key to a Better South African Future - Yuningsih, Siti Hadiaty; Yohandoko, Setyo Luthfi; Pirdaus, Dede Irman (International Journal of Research in Community Services, 2024)
South Africa, a country rich in history and natural beauty, also faces serious challenges in the health sector, especially maternal and child health. Maternal and infant mortality rates are still high, inequality in access to health services, low levels of education and knowledge of reproductive health, as well as problems of malnutrition and HIV/AIDS are the main focus of discussion. Although the government has launched programs to improve maternal and child health, funding challenges and disparities in health resources between regions still hinder the achievement of equitable health coverage. This article highlights the importance of increasing health budget allocations, building first-level health facilities, improving the skills of health workers, reproductive health education, nutritional interventions, and multi-stakeholder cooperation to overcome these health challenges.